Pengaruh Suasana Toko, Lokasi, Dan Pelayanan Terhadap Minat Beli Konsumen Koya Baby House Dikota Bengkulu - Liberty Tania Tania; Syofian Syofian; Markoni Markoni (STIE AMKOP, 2023)
The purpose of this study is to find out how much influence the shop atmosphere, location and service have on the buying interest of Koya Baby House consumers in the city of Bengkulu. The variables of this study are Store Atmosphere, Location and Service. The method used in this research is distributing questionnaires. This research is a quantitative approach research. The research population was all consumers who visited the Koya Baby House store in Bengkulu City, 140 samples using the accidental sampling method. The analytical tool used in this study uses SPSS 16. The data analysis method used is multiple linear regression. The results showed that (1) Store atmosphere did not have a significant effect on the Buying Interest of Koya Baby House Consumers in the City of Bengkulu, (2) Location had a significant effect on the Buying Interest of the Koya Baby House Consumers in the City of Bengkulu, (3) Service did not have a significant effect on the Buying Interest of Koya Consumers Baby House in Bengkulu City, (4) Store Atmosphere, Location and Services simultaneously influence the Buying Interest of Koya Baby House Consumers in Bengkulu City. keywords: Store Atmosphere, Location, Service, Purchase Intention